Chimurenga War names as parodic critique of imperialism - Viriri, Advice (Unisa Press, 2016)
A dictionary of Chimurenga War names by Charles Pfukwa is one of my prize possessions. Dr Charles Pfukwa is a Chimurenga War polymath whose encyclopaedic knowledge of the liberation struggle is unquestionable. He is an associate professor of linguistics, an internationally renowned author and a dominant figure in Zimbabwean print media, being Chief Editor of The Patriot, which has a uniquely large readership among Zimbabweans because of its policy of sharpening people’s national consciousness. The dictionary will no doubt generate much interest among all who conceive of national and cultural identity in linguistic terms, regardless of their age. Writers across the African continent have debated the extent to which they should be, in Nadine Gordimer’s phraseology,“ more than writers” (1989), as well as their commitment and responsibility to examine topical issues.To many readers, the dictionary offers a therapeutic, leisure-time activity and an essentially optimistic perspective of humanity’s potential to transform the debilitating effects of colonialism.